Techniques Used by EFL Teachers While Teaching Children English: A Case on Primary School Level - Rabab Sabri Shahbon, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This study is set to investigate the techniques employed by EFL teachers when teaching English to kids. For the sake of the study, a questionnaire is designed to investigate the problem in question. The questionnaire was then administered to 10 primary school teachers who have been teaching EFL to kids for a number of years. The quantitative data was collected and analysed by descriptive statistics and results were obtained. One finding of the study is that the most commonly used techniques by the teachers in the classroom are those of the Grammar Translation approach. The findings of the study also demonstrate that most participants neglected using the target language as a medium of instruction. Moreover, about 80% of the sample gave no emphasis to aural comprehension. On the whole, the focus of the teacher in the classroom is shifted from enabling learners to effectively and appropriately communicate in English to prolonged explanation of grammatical rules.